World Conference on Women in Nairobi: New Strategies for Women’s Studies - Irene Kamberidou (SPOTLIGHT, A Fortnightly Publication for Political Studies, Publication of the Institute of Political Studies (I.P.S), no. 17, Feb. 1, 1985: 8., 1985)
Kamberidou, Irene (1985). World Conference on Women in Nairobi: New Strategies for Women’s Studies” SPOTLIGHT, A Fortnightly Publication for Political Studies, Publication of the Institute of Political Studies (I.P.S), no. 17, Feb. 1, 1985: 8.